Dramatic X-ray spectral variability of a Compton-thick type-1 QSO at z ∼ 1. Issue 4 (17th August 2018) - Simm, T; Buchner, J; Merloni, A; Nandra, K; Shen, Y; Erben, T; Coil, A L; Willmer, C N A; Schneider, D P
ABSTRACT: We report on the discovery of a dramatic X-ray spectral variability event observed in a z ∼ 1 broad line type-1 QSO. The XMM - Newton spectrum from the year 2000 is characterized by an unobscured power-law spectrum with photon index of Γ ∼ 2, a column density of N_H5× 10^20 cm^-2, and no prominent reflection component. Five years later, Chandra captured the source in a heavily-obscured, reflection-dominated state. The observed X-ray spectral variability could be caused by a Compton-thick cloud with N_H2× 10^24 cm^-2 eclipsing the direct emission of the hot corona, implying an extreme N H variation never before observed in a type-1 QSO. An alternative scenario is a corona that switched off in between the observations. In addition, both explanations require a significant change of the X-ray luminosity prior to the obscuration or fading of the corona and/or a change of the relative geometry of the source/reflector system. Dramatic X-ray spectral variability of this kind could be quite common in type-1 QSOs, considering the relatively few data sets in which such an event could have been identified. Our analysis implies that there may be a population of type-1 QSOs which are Compton-thick in the X-rays when observed at any given time.